2012
DOI: 10.1021/ma202587z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Brush-Shaped Hybrid Inorganic/Organic Polymers Based on Polyphosphazenes

Abstract: A series of densely grafted star-and combshaped molecular brushes composed of polystyrene, poly(tertbutyl acrylate), and poly(N-isopropylacrylamide) were prepared by atom transfer radical polymerization (ATRP) using either cyclotriphosphazenes or polyphosphazenes as initiators. The initiators were prepared by the introduction of a free hydroxyl group into the side chains of a phosphazene cyclic trimer and polymer, followed by esterification with 2-bromopropionyl bromide. The grafting conditions were optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…When a PNIPAM segment is attached to another hydrophilic block, for example, poly(ethylene glycol) (PEG), these block copolymers can dissolve in water under the LCST and self‐associate to stable morphologies such as micelles and vesicles upon heating . On the other hand, if the PNIPAM block is conjugated to hydrophobic polymer blocks, the resultant copolymers can form assemblies at room temperature which can further aggregate into complex morphologies at high temperatures . Several studies reported on synthesis and assembly of triblock copolymers containing temperature‐responsive polymer segments .…”
Section: Introductionmentioning
confidence: 99%
“…When a PNIPAM segment is attached to another hydrophilic block, for example, poly(ethylene glycol) (PEG), these block copolymers can dissolve in water under the LCST and self‐associate to stable morphologies such as micelles and vesicles upon heating . On the other hand, if the PNIPAM block is conjugated to hydrophobic polymer blocks, the resultant copolymers can form assemblies at room temperature which can further aggregate into complex morphologies at high temperatures . Several studies reported on synthesis and assembly of triblock copolymers containing temperature‐responsive polymer segments .…”
Section: Introductionmentioning
confidence: 99%
“…[32] Such bottle-brush type organic-inorganic hybrid polymers can also be prepared via a "grafting-from" approach, polymerizing away from the functionalized polyphosphazene backbone, for example via atom transfer radical polymerization (ATRP) from alkyl bromide group functionalized polyphosphazenes. [58] Such high density bottle brush polymers could have wide reaching applications, one example of which includes quaternized organicinorganic hybrid brush polyphosphazenes being investigated for their antibacterial properties. [59] A "grafting-to" approach has also been achieved, via polyphosphazenes coupled onto branched organic polymers such as phosphoranimine-terminated poly(amidoamine) (PAMAM) dendrimers via cationic polymerization.…”
Section: Branched Polyphosphazenesmentioning
confidence: 99%
“…[15][16][17][18][19][20] It is well known that phosphazene-containing polymers have been widely used as the optical materials, biomaterials, membrane materials, electrical and electrochromic materials, hybrid materials, etc., because of their superior high thermal stability and biocompatibility of the inorganic unit and inconceivable structural diversity. Presence of the inorganic phosphazene (-P=N-) unit in macromolecular backbones and the structural multiplicity of side groups, such as organic, organometallic or inorganic units, provides tremendous flexibility to functionalize the materials through physical or chemical modifications for numerous applications.…”
Section: Introductionmentioning
confidence: 99%